A new species of Zaglyptogastra Ashmead (Hymenoptera: Braconidae: Braconinae) from Thailand - Chansri, Kittipum; Quicke, Donald L. J.; Butcher, Buntika A. (Zootaxa, 2022)
Zaglyptogastra Ashmead, 1900 was erected for a large, distinctive Braconinae wasp, Z. abbotti, collected in Lower Siam (Thailand) (Ashmead 1900). Although nine species are known from the Indo-Australian region, only three are recorded from mainland Indochina: Z. abbotti Ashmead, 1990 (Thailand), Z. vitalisi (Turner, 1919) (Thailand, Laos) and Z. vietnamica Long & Mai, 2015 (Vietnam) (El-Heneidy & Quicke, 1991; Long & Mai, 2015). In 2021, two further Asia species, Z. exilis Li, van Achterberg & Chen, 2021 and Z. tricolor Li, van Achterberg & Chen, 2021 were described from China (Li et al. 2021).